Enhancing Mental Toughness through Appreciative Inquiry among Pencak Silat Athletes of Persinas ASAD - Rahma, Uslarika Hida; Azmi, Muhammad Mursyidul; Utama, Muhammad Elmi; Triastuti, Elizabeth Pinkan Rachma (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
This study aims to determine the effectiveness of appreciative inquiry interventions in strengthening athlete mental toughness. The subjects in the study were Persinas Asad pencak silat athletes with a total of 40 athletes. The experimental research design used One Group Pretest-Postest using all subjects as the experimental group. Data analysis used Paired Sample T-Test, based on the results of pretest and posttest data. The results of this study indicate that appreciative inquiry has a significant impact, athletes are able to design future dreams and are able to develop strategies to make changes. The statistical results show a p value = 0.000 < 0.05, meaning that appreciative inquiry is effective in strengthening the mental toughness of Persinas Asad martial arts athletes. The implication of this study is that this approach not only helps athletes recognize their best potential but also encourages them to set future visions and formulate realistic and directed strategies for achievement.